Hubungan antara Menulis Huruf Tegak Bersambung pada Kemampuan Membaca Siswa Sekolah Dasar - Putri, Aisah Diana; Rigianti, Henry Aditia (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
In this modern and convenient digital era, cursive writing is still an interesting topic of discussion. Despite that, cursive writing has many benefits for students, especially in improving reading skills. This literature review aims to explore the relationship between cursive writing and the reading ability of elementary school students. The research method used in this study is literature review, with techniques for collecting, analyzing, and concluding relevant information. From this literature review, it is revealed that cursive writing can train visual-motor skills, spatial visualization, spelling, cognitive skills, and understanding of writing, thus improving students' reading ability. In addition, cursive writing can also activate the brain's synaptic network in students, allowing them to remember information read for a longer period. Students' patience can also be honed through cursive writing activities. Therefore, cursive writing can be an effective strategy to improve students' reading ability.